Immigration and School Choices in the Midst of the Great Recession - Lídia Farré; Francesc Ortega; Ryuichi Tanaka (Institute for the Study of Labor (IZA), 2015)
This paper empirically analyzes the effects of immigration on the schooling decisions of natives. We employ household-level data for Spain for years 2000-2012, a period characterized by a large immigration wave and a severe recession. Our estimates reveal that Spanish households responded to immigration by increasing their educational expenditures. This result was mainly driven by an important native flight from tuition-free schools toward private ones. We also find strong evidence of cream-skimming: only the more educated native households switched to private schools in response to immigration. Finally, our simulations suggest that the reduction in household income due to the Great Recession mitigated the flight toward private schools triggered by immigration but was not enough to offset it. We argue that these findings are driven by several factors: school assignment rules, concerns over negative peer effects, and political economy forces.
Keywords: D7; F22; H52; H75; J61; I22; I24; 330; education; public school; recession; immigration